IMPACT OF GLOBLISATION ON TRADE AND INVESTMENT IN INDIA (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
The turning point in India's globalization journey came in 1991, when economic liberalization policies opened doors to foreign trade and investment. The present study explores the impact of globalization on trade and investment and study the challenges and future prospects of Indian trade and investment, the study considers the ten years periods starting from 2013-14 to 2023-24 and the study is exploratory in nature and mainly based on the secondary data which is collected through various sources as like scholarly research papers, international databases and government statistics for examination. The study indicate that India's economy has diversified, modernized and become globally competitive. However, challenges like trade deficits, income inequality and external economic dependencies remain areas to address. The study also found that the India’s trade has grown consistently, except for brief downturns due to global uncertainties. Policy reforms and global integration contributed to long-term trade expansion. Future trade growth will depend on geopolitical stability, supply chain efficiency and continued investment in export-driven industries. Further study found that India’s investment growth has shown resilience, recovering from downturns and global uncertainties and during 2017-19 declines indicate vulnerabilities, highlighting the need for stronger domestic investment policies and Future growth prospects remain high, especially in sectors like digital economy, manufacturing and sustainable energy. India's trade and investment future depends on policy stability, infrastructure improvements, and global partnerships. Strategic reforms will help India maintain its position as a competitive global economic player.